Pelestarian Bahasa Melayu Ambon di Kota Ambon - Marleen Muskita; Susana Magdalena Welly Muskita (BADATI, 2022)
Ambonese Malay is one of the regional languages spoken by the people in Maluku Province, and is classified as a family of standard Malay languages spoken in the Maluku Province. As time goes by, it is undeniable that the times have made the new generation lack of understanding of the language that has been handed down by its predecessors, the gap in understanding between the two generations arises due to the non-smooth transfer of group communication from generation to generation. Many young people cannot use Ambonese Malay well and some do not understand the meaning of some Malay words, and they also prefer to use mixed languages. The purpose of this study was to find out how to preserve the Ambonese Malay language in Ambon City. This study uses a qualitative descriptive research type. From the results of the research, it can be seen that there is still preservation of the Ambonese Malay language in the community. Although there is preservation of the Ambonese Malay language, there are still obstacles found by the community in using Malay as a language to facilitate communication, according to some informants sometimes when used in the communication process the meaning is not understood by children because it is considered a new vocabulary for them. them, besides that, their dialect pronunciation is too fast and some in the surrounding environment no longer use Ambonese Malay so that the communication process is a bit hampered.